Analisis Pengukuran Kualitas Pelayanan Sistem Informasi Perbankan Dengan Menggunakan Cobit 5 - Elyana, Instianti (STIKOM Tunas Bangsa Pematangsiantar, 2017)
The role of information technology today is very necessary especially for companies that are service-based. With the development of technology and technology utilization of course can improve banking services to be better. The field of development and Information Technology is a part that will manage the Information Technology in the Company in the field of banking. Standard and banking procedures, especially in the field of service and security performance measurement of information technology using COBIT 5 Framework. So with the measurement of service quality Information System to customers can provide enter to the company and is expected to contribute suggestions and recommendations to the management proposal. that the current banking services have a good standard of Information Technology and need to improve the information system better.